First Aid Awareness Campaign for Two Undergraduate Nursing Cohorts - Mona H. Afifi; Rama E. Dela; Yara A. Al Qahtani; Afnan Al Dosary; Amnah Y. Hamdi (Evidence-Based Nursing Research)
Context: First aid is an emergency measure of saving a life, preventing further deterioration, and promoting recovery of the victim before professional medical help is initiated.  Awareness campaigns are significant community efforts to raise awareness of community groups regarding critical concerns.